Are endocasts reliable proxies for brains? A 3D quantitative comparison of the extant human brain and endocast. Issue 2 (30th September 2020) - Dumoncel, Jean; Subsol, Gérard; Durrleman, Stanley; Bertrand, Anne; de Jager, Edwin; Oettlé, Anna C.; Lockhat, Zarina; Suleman, Farhana E.; Beaudet, Amélie
Abstract: Endocasts (i.e., replicas of the inner surface of the bony braincase) constitute a critical proxy for qualifying and quantifying variations in brain shape and organization in extinct taxa. In the absence of brain tissues preserved in the fossil record, endocasts provide the only direct evidence of brain evolution. However, debates on whether or not information inferred from the study of endocasts reflects brain shape and organization have polarized discussions in paleoneurology since the earliest descriptions of cerebral imprints in fossil hominin crania. By means of imaging techniques (i.e., MRIs and CT scans) and 3D modelling methods (i.e., surface‐based comparisons), we collected consistent morphological (i.e., shape) and structural (i.e., sulci) information on the variation patterns between the brain and the endocast based on a sample of extant human individuals (N = 5) from the 3D clinical image database of the Steve Biko Academic Hospital in Pretoria (South Africa) and the Hôpitaux Universitaires Pitié Salpêtrière in Paris (France). Surfaces of the brain and endocast of the same individual were segmented from the 3D MRIs and CT images, respectively. Sulcal imprints were automatically detected. We performed a deformation‐based shape analysis to compare both the shape and the sulcal pattern of the brain and the endocast. We demonstrated that there is close correspondence in terms of morphology and organization between the brain and the corresponding endocast with the exception of the superior region. By comparatively quantifying the shape and organization of the brain and endocast, this work represents an important reference for paleoneurological studies. Abstract : Is the endocast a reliable proxy for reconstructing the brain of fossil specimens? By quantitatively comparing extant human brains and endocasts using MRIs and CT‐scans, here we address this fundamental question and support the significance of fossil endocasts in paleoneurological studies.